Gestión administrativa en el GAD parroquial rural de Membrillo periodo 2014 – 2017 - Solórzano Vera, Delia Josefa (2019)
The research aimed to evaluate the administrative management of the GAD Rural Parish of Membrillo period 2014 - 2017, for institutional strengthening. Under the provisions, the information was collected through the inductive, deductive and analytical methods, which with their process helped to develop the explicit activities in the investigation. For this purpose, the budgetary analysis of the periods 2014, 2015, 2016 and 2017 was generated, where it was identified that the government entity, despite paying income sources, does not have sufficient financial capacity to meet the needs of the population of the Parish. In the same way for the slogan of the result, techniques such as the interview were used, which allowed to know the quality of administrative management provided by the government entity. Together with the above, the survey was applied to the inhabitants of the same community, where through statistical data the efficiency, effectiveness and quality available in public resources was exhibited through the administrative management of the Rural Parish GAD of Membrillo. From these indications it is constituted that the government entity must promote self-management, so that the fulfillment of the requirements requested by the population improves, and that allows to reach the desired percentage in financial autonomy.